Composition and Properties of Fibre Extracted from Pseudostem of Banana (Musa Sp.) - S Shivashankar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2006)
Pseudostem waste from five commercial cultivars of banana was used to extract fibre in order to study its properties. Fibre was extracted by decortification of sheath either manually or using Raspador machine. Yield of fibre in cultivars varied from 0.548% to 0.891%. There was no significant difference in the yield of fibre from different layers of sheath although differences among cultivars were significant. Cellulose was the major component of the fibre at about 60% while lignin levels were nearly 20%. The strength characteristics of Nendran fibre like, mean breaking load, mean breaking extension and tenacity were comparable to those reported for other naturally occurring plant fibres such as pineapple, jute and sisal. The study highlighted the importance of exploiting banana pseudostem after harvest of banana bunch for fibre production on a commercial scale.